Sensitivity of the rate of nutrient uptake by chemotactic bacteria to physical and biological parameters in a turbulent environment. (21st December 2015) - Watteaux, Romain; Stocker, Roman; Taylor, John R.
Abstract: In this study, we use direct numerical simulations (DNS) to investigate the response of chemotactic bacteria to an isolated patch of chemoattractant in a turbulent environment. Previous work has shown that by stirring nutrients that are chemoattractants into a network of thin, elongated filaments, turbulence directly influences the rate at which chemotactic bacteria consume nutrients. However, the quantitative outcome of this process is influenced by a host of physical and biological factors, and many of these remain unexplored. Here, we analyse the sensitivity of nutrient uptake by chemotactic bacteria on a wide range of physical and biological parameters using a series of controlled DNS. Starting with uniformly distributed populations of motile and non-motile bacteria in a fully developed homogeneous, isotropic turbulent flow, we inject a patch of dissolved nutrients. We then assess the chemotactic advantage, defined as the difference between the nutrients consumed by motile and non-motile bacteria over the lifetime of the patch. We find that the chemotaxis can enhance the total uptake rate by a factor of 1.6 and allows the population of chemotactic bacteria to absorb nutrients 2.2 times faster than non-motile bacteria Results show that chemotactic bacteria are subject to a trade-off between swimming to leave regions devoid of nutrients and, once a nutrient gradient is detected, staying in regions of large nutrient concentration. These findings could help explain how the physical characteristics of turbulent marine ecosystems influence the optimal biological traits of bacteria through the competition for limited resources. Abstract : Graphical abstract: Abstract : Highlights: The sensitivity of nutrient uptake by chemotactic bacteria is explored. High concentrations of bacteria form in thin filaments co-located with regions of high nutrients. Chemotaxis can increase the instantaneous nutrient uptake rate by approximately a factor of two. The uptake advantage arising from chemotaxis saturates at large values of some parameters.